Revisión taxonómica del género Campylocentrum (Orchidaceae: Angraecinae) en Costa Rica - Bogarín Chaves, Diego Gerardo 1982- (2010)
A taxonomic revision of Campylocentrum (Orchidaceae) in Costa Rica is presentad. Campylocentrum is characterized by epiphytic, monopodial plants with indefinite terminal growth. Either elongated, distichously leafy or acaulescent, leafless stems are present. The leaves are conduplicate, rarely terete, articulate with the sheath surrounding the stem, sometimes absent or reduced to scale-like leaves along an elongated stem. The inflorescences are lateral racemes with distichously arranged spurred-lip flowers on the rachis. The taxonomic history of the genus and its phylogenetic position are discussed. Characters of vegetativa and floral morphology are treated, and their taxonomic significance is discussed. The genus is treated as comprising nine species in the country, anda key to species is provided. Each taxon is described on the basis of Costa Rican material, illustrated in a composite plate, and its distribution in the country is assessed. Distribution maps for all the taxa are given. Overall distribution, derivation of name, notes on species ecology, and diagnostic features are presentad for each taxon. Two species need to be lectotipifyed: C. parvulum and C. multiflorum. A new species from Costa Rica has been documentad and is here illustrated. lt is similar to Campylocentrum pachyrrhizum but differs in having a congested inflorescence, the spur of the lip curved upward, narrow at base and wider at apex, and obscurely three lobed.